2021
DOI: 10.1080/08911762.2021.1958277
|View full text |Cite
|
Sign up to set email alerts
|

Do Consumers Really Care about Aspects of Corporate Social Responsibility When Developing Attitudes toward a Brand?

Abstract: the present study assesses the relationship between the dimensions of perceived corporate social responsibility (PcsR) and consumer perceptions about a brand. the approach taken herein for PcsR is based on the sustain-centric paradigm. Under this model, PcsR comprises three dimensions: economic, social, and environmental. accordingly, a system of 11 hypotheses embedded in a conceptual framework is proposed and empirically tested. Measurements for the constructs in the hypotheses are assessed using a structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…This can also be explained by the high proximity of the health and education domains, as donations to hospitals or schools are more related to CSR’s social and economic dimensions. For example, Vera-Martínez et al . (2021) have pointed out that CSR’s economic and social dimensions significantly influence perceived CSR, while consumers may disregard other topics such as environmental responsibilities.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can also be explained by the high proximity of the health and education domains, as donations to hospitals or schools are more related to CSR’s social and economic dimensions. For example, Vera-Martínez et al . (2021) have pointed out that CSR’s economic and social dimensions significantly influence perceived CSR, while consumers may disregard other topics such as environmental responsibilities.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…Besides, various CSR domains can impact consumer–brand relationships differently (Shankar and Yadav, 2020). However, studies that examine the effects of specific CSR actions on consumer perceptions, attitudes, CBBE and supportive communication intent are relatively scarce (Sen and Bhattacharya, 2001; McDonald and Lai, 2011; Staudt et al ., 2014; Vera-Martínez et al ., 2021). Examining the impacts of CSR actions on CSR perceptions and CBBE is beneficial for researchers and marketing managers to understand the drivers of brand equity, the main element of competitive advantage and financial outcomes (Cho and Hwang, 2020) because consumers are among the primary stakeholders of an organization (Dang et al ., 2020) and CSR influences customer commitment in banking (Shah and Khan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Corporate BC also mediates the relationship between CSR and corporate reputation. Vera-Martínez, Alvarado-Herrera, and Curras-Pérez [22] used the sustainability-centric paradigm to explain how perceived CSR affects BC. Zayyad et al [6] confirmed the relationship between CSR and BC, they also suggested that banks that practice CSR for the benefit of their stakeholders, society, and the environment can increase their BC, which ultimately affects patronage intentions positively, including word of mouth and repurchase intentions.…”
Section: Literature Review and Hypothesis Development 21 Csr Perceptions And Brand Credibility Brand Reputation And Brand Equitymentioning
confidence: 99%
“…Moreover, the result of H2 revealed that PCSR has a significant and positive impact on developing brand attitudes in the retail industry; this supports the previous results of Aydın (2019). Additionally, a study by Vera-Martínez et al (2022) found that both economic and social CSR have a positive effect on attitude towards brands in the retail industry.…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides strong evidence for the effect of CSR awareness on consumer attitude towards a brand (Vera-Martínez et al, 2022); this operates as a chain of cognition (beliefs) and affect (feelings), leading to Gen Y's purchase intention (Ocass and Choy, 2008). However, CSR awareness of consumers does not necessarily guarantee a positive purchase decision simply because a brand is involved in CSR initiatives; a brand must be genuinely committed to CSR.…”
Section: Gen Y's Corporate Social Responsibility Attitude As a Modera...mentioning
confidence: 99%